DERIVASI PERSAMAAN MATEMATIS DALAM PENDUGAAN NILAI KONSUMSI HARIAN PENYU HIJAU DI PADANG LAMUN BERDASARKAN PENGAMATAN AKTIFITAS MAKANNYA - Roem, Muhamad (Jurnal Harpodon Borneo, 2012)
Tremendous gaps remain in our understanding of the foraging ecology of sea turtles. For some species, little progress in the elucidation of diet and foraging habitats has been made since reviews summarized the state of our knowledge more than 20 years ago. These papers will describe how to derivate a mathematics equation to estimate the grazing rate of green sea turtle in a seagrass meadow. The mathematical equation was generated based on observation on the green sea turtle daily feeding activity which correlated with average total time that they allocated for feeding or foraging activity. Through these mathematical equations we can estimate total daily consumption of green sea turtle. Keywords :  mathematic, equation, grazing rate, green sea turtle, feeding activity